Manajemen Pembiayaan Pendidikan Sekolah di Indonesia - Rukimin (PT. Penerbit Tiga Mutiara, 2024)
This article aims to comprehensively explore the management of education financing in schools across Indonesia. The research adopts a literature review approach, gathering data through meticulous source searches and synthesizing information from diverse references, including books, journals, and previous research. The findings of this study reveal that the education budget encompasses the allocation of funds used to facilitate educational services. Whether for public schools or governmental entities (at both central and regional levels), the authority for budget utilization is governed by legal frameworks. Nationally, the Ministry of Education and Culture (Kemendikbud) and the Ministry of Research, Technology, and Higher Education (Kemenristek Dikti) play pivotal roles in determining the education budget, specifying its sources and objectives. At the regional level, Provincial, District, and City governments, through the Education Service Unit (Satker Dinas Pendidikan), are accountable for planning and overseeing the utilization of education budgets in line with their respective jurisdictions and discretion. Simultaneously, at the school level, active involvement in planning and executing agreed-upon school programs funded by the budget is undertaken by the school principal in collaboration with the school community.